Wired into Nature : The Telegraph and the North American Frontier - Schwoch, James, 1955- (Book collections on Project MUSE., 2018)
The completion of the Transcontinental Telegraph in 1861 completed telegraphy's mile-by-mile trek across the West. In addition to linking the coasts, the telegraph represented an extraordinary American effort in many fields of endeavor to know, act upon, and control a continent. Merging new research with bold reinterpretation, James Schwoch details the unexplored dimensions of the frontier telegraph and its impact.